Applicability of currently available flare radiation models for hydrogen and syngas. Issue 2 (30th July 2014) - Miller, Derek; Jung, Seungho; Lutostansky, Elizabeth
<x xml:space="preserve">Abstract</x> The primary purpose of a flare model is to provide a reasonably accurate prediction of radiant heat flux at any point of interest around the flame in order to be able to define safe release locations. In order to do this, a flare model needs to provide a good prediction of the following critical flame parameters: flame length, flame tilt, and radiant heat fraction, including the impact of wind and release orientation on these parameters. In addition, the model needs to distribute the radiant heat along the flame in a reasonably realistic way and to allow for the transmissivity of the ambient air. Industry standard models for vertical flares include Chamberlain [Chamberlain, Chem Eng Res Des 65 (1987)], API 521 [API STANDARD 521, Pressure‐Relieving and Depressuring Systems, 6th Edition, American Petroleum Institute, Washington DC, 2014], and Brzustowski & Sommer [API STANDARD 521, Pressure‐Relieving and Depressuring Systems, 6th Edition, American Petroleum Institute, Washington DC, 2014]. These models were originally developed primarily based on hydrocarbon data. Several commercially available consequence models allow the use of these models for all flammable materials. Due to the lack of other options, these commercially available consequence software models are often applied to hydrogen, syngas (hydrogen/carbon monoxide mixtures), and other materials that are well outside the intended scope of the models. A review has been performed to evaluate applicability of the Chamberlain, API 521, and Brzustowski & Sommer models to hydrogen and syngas, including comparison with limited published data. As a result of this review, a number of significant concerns have been identified. This has led to initiation of a new test program to collect data specifically for hydrogen and syngas and the subsequent development of new models. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 141–146, 2015